Professional skepticism as a mediator between brainstorming sessions and audit quality: case of Jordan / Ashraf Bataineh - Bataineh, Ashraf (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
The study aimed to measure the effect of professional skepticism practice; as a mediator between brainstorming sessions and audit quality at auditing offices and firms in Jordan. The researcher studied the effect of using all brainstorming sessions (open, round-robin, electronic) on improving audit quality in light of professional skepticism practice at every stage of the audit process. The researcher developed and distributed a questionnaire on a random sample of 216 Jordanian auditors practicing the auditing profession for data collection purposes. The study results indicated the effect of brainstorming sessions in light of professional skepticism on improving the quality of auditing, and found that the most influential of them was the round-robin brainstorming with an effect of (0.300), followed by electronic brainstorming with an effect of (0.233), and then open with an effect of (0.224). Accordingly, the researcher recommends that scientific and proficient staffs should reconsider procedures followed in auditing process and develop them to ensure that auditors are obligated to apply brainstorming sessions on all audit items and stages, especially procedures for practicing professional skepticism whenever making an audit of companies’ financial statements.